Using biomarkers and early prophylactic treatment to prevent cardiotoxicity in cancer patients on chemotherapy - Bacchiani, Giulia; Cardinale, Daniela (SA Heart Journal, 2017)
Cardiac toxicity induced by anticancer therapy is of considerable concern for, once it develops, it may compromise the clinical effectiveness of treatment independent of the oncologic prognosis. The main strategy to minimize cardiotoxicity is to detect high-risk patients and begin prophylactic treatment as early as possible. According to the current standard for monitoring cardiac function cardiotoxicity is usually detected only once a functional impairment has already occurred, thus precluding any chance of prevention. The measurement of cardio-specifi c biomarkers can be a valid diagnostic tool for the early identifi cation, assessment and monitoring of cardiotoxicity. The role of Troponin I in identifying patients with subclinical cardiotoxicity and their subsequent treatment with angiotensin- converting enzyme inhibitors to prevent left ventricular ejection fraction (LVEF) reduction and cardiac events, is emerging as an effective strategy against these complications. When this approach is not feasible, a complete LVEF recovery and a reduction in cardiac events may be achieved if left ventricular dysfunction (LVD) is detected early and the patient promptly treated with angiotensin-converting enzyme inhibitors, possibly in combination with beta-blocking agents.